2021
DOI: 10.1083/jcb.202104093
|View full text |Cite
|
Sign up to set email alerts
|

Signal strength controls the rate of polarization within CTLs during killing

Abstract: Cytotoxic T lymphocytes (CTLs) are key effector cells in the immune response against viruses and cancers, killing targets with high precision. Target cell recognition by CTL triggers rapid polarization of intracellular organelles toward the synapse formed with the target cell, delivering cytolytic granules to the immune synapse. Single amino acid changes within peptides binding MHC class I (pMHCs) are sufficient to modulate the degree of killing, but exactly how this impacts the choreography of centrosome pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 60 publications
(102 reference statements)
0
20
0
1
Order By: Relevance
“…TCR triggering with low-affinity ligands leads to impairment of lytic granule polarization towards the MTOC ( 128 ), whereas only high-avidity interactions give rise to granule recruitment to the polarized centrosome at the synapse. Moreover, increased signal strength leads to an increased proportion of CTLs, where TCR strength modulates the rate but not the organization of effector CTL responses ( 129 ). Consistent with these findings, a study in CD4 T cells also found that stronger TCR signals resulted in decreased levels of PIP2 ( 130 ).…”
Section: The Immune Synapse Formed By Cd4 Ctlsmentioning
confidence: 99%
“…TCR triggering with low-affinity ligands leads to impairment of lytic granule polarization towards the MTOC ( 128 ), whereas only high-avidity interactions give rise to granule recruitment to the polarized centrosome at the synapse. Moreover, increased signal strength leads to an increased proportion of CTLs, where TCR strength modulates the rate but not the organization of effector CTL responses ( 129 ). Consistent with these findings, a study in CD4 T cells also found that stronger TCR signals resulted in decreased levels of PIP2 ( 130 ).…”
Section: The Immune Synapse Formed By Cd4 Ctlsmentioning
confidence: 99%
“…The actin cytoskeleton is found to be indispensable for cytotoxic granule secretion and can act as an indicator for antigen‐binding strength. Although higher antigen specificity can lead to faster Ca 2+ flux, the sequence of events in antigen recognition is identical regardless of its specificity 138 . This series of studies highlight the essential roles 4D imaging plays in our understanding of effector T cell function, which provides critical information to potentially optimize immunotherapy such as CAR T cell therapy.…”
Section: Deconstruction Of Lymph Node To Understand T Cell Migration ...mentioning
confidence: 93%
“…Although higher antigen specificity can lead to faster Ca 2+ flux, the sequence of events in antigen recognition is identical regardless of its specificity. 138 This series of studies highlight the essential roles 4D imaging plays in our understanding of effector T cell function, which provides critical information to potentially optimize immunotherapy such as CAR T cell therapy. The exquisitely high resolution of the LLSM platform allows these same imaging and analysis pipelines to be repurposed toward understanding how to cells reach their infected or cancerous targets.…”
Section: Capturing Cells In Motionmentioning
confidence: 99%
“…TCR engagement on CTLs triggers centrosome polarisation towards the contact with the target cell and its close apposition to the synaptic membrane in a process tightly regulated by the actin and tubulin cytoskeletons, which sets the stage for the dynein- and AP-3-dependent transport of LGs to the immunological synapse (IS) center ( 26 , 27 ), as well as by TCR signal strength ( 28 ). Interestingly, rapid LG secretion on target cell encounter can occur in the absence of centrosome polarisation, which is instead essential for the establishment of stable, stimulatory synapses ( 29 ), suggesting an alternative mechanism for LG mobilisation to the target cell contact.…”
Section: The Arsenal Of Ctlsmentioning
confidence: 99%